RESEÑA de : Blackledge, P.; Knight, K. (eds.). Virtue and Politics : Alasdair MacIntyre’sRevolutionary Aristotelianism. Indiana : University of Notre Dame Press, 2011 - Ramis Barceló, Rafael (ENDOXA, 2011)
_